High Zoom Ratio Foveated Snapshot Hyperspectral Imaging for Fruit Pest Monitoring - Yaoyao Hu; Jun Chang; Yiting Li; Wenchao Zhang; Xiaoxiao Lai; Quanquan Mu (Journal of Spectroscopy)
Snapshot hyperspectral imaging technology is increasingly used in agricultural product monitoring. In this study, we present a 9× local zoom snapshot hyperspectral imaging system. Using commercial spectral sensors with spectrally resolved detector arrays, we achieved snapshot hyperspectral imaging with 14 wavelength bands and a spectral bandwidth of 10–15 nm. An experimental demonstration was performed by acquiring spatial and spectral information about the fruit and Drosophila. The results show that the system can identify Drosophila and distinguish well between different types of fruits. The results of this study have great potential for online fruit classification and pest identification.